Tracing Intertextuality Between “Aisyah Istri Rasulullah” and Umdatul Choirot’s Al-Madh Li-‘Aisyah Binti Abi Bakr - Muhammad Ziyad Hubbillah; Ahfa Rahman Syah; Muhammad Faidhur Rahman (UIN Syarif Hidayatullah Jakarta, 2026)
This study investigates the intertextual dialogue between the viral song